Biofilm shows spatially stratified metabolic responses to contaminant exposure - Cao, Bin (2012)
Biofilms are core to a range of biological processes, including the bioremediation of environmental contaminants. Within a biofilm population, cells with diverse genotypes and phenotypes coexist, suggesting that distinct metabolic pathways may be expressed based on the local environmental conditions in a biofilm. However, metabolic responses to local environmental conditions in a metabolically active biofilm interacting with environmental contaminants have never been quantitatively elucidated. In this study, we monitored the spatiotemporal metabolic responses of metabolically active Shewanella oneidensis MR-1 biofilms to U(VI) (uranyl, UO(2)(2+)) and Cr(VI) (chromate, CrO(4)(2−)) using noninvasive nuclear magnetic resonance imaging (MRI) and spectroscopy (MRS) approaches to obtain insights into adaptation in biofilms during biofilm-contaminant interactions. While overall biomass distribution was not significantly altered upon exposure to U(VI) or Cr(VI), MRI and spatial mapping of the diffusion revealed localized changes in the water diffusion coefficients in the biofilms, suggesting significant contaminant-induced changes in structural or hydrodynamic properties during bioremediation. Finally, we quantitatively demonstrated that the metabolic responses of biofilms to contaminant exposure are spatially stratified, implying that adaptation in biofilms is custom-developed based on local microenvironments.